Development of a scale for evaluating the severity of disfigurements caused by injuries disease or surgery - Rakic, Vesna S.; Đikanović, Bosiljka; Alempijević, Djordje; Simić, Radoje; Bogdanović, Slobodan; Janjić, Zlata; Vulović, Dejan (Vojnosanitetski pregled, 2020)
Background/Aim. Medico-legal aspect of physical disfigurements has been subject of few scientific researches. The aim of this study was to establish a standardized instrument for forensic evaluation of all kinds of physical disfigurements, which has not existed until now. Methods. The research was conducted in 3 phases: the first one – drafting a list of disfigurements; the second phase – evaluation of the draft of the disfigurement list provided by 11 experts (plastic surgery lecturers) by the use of the Delphy method; the third one during which 51 medical doctors, members of Serbian Association of Plastic, Reconstructive and Aesthetic Surgery were evaluating the list of disfigurements. Results. Totally 176 individual physical disfigurements were described in the first phase of research. In the second phase, 217 disfigurements were established which were classified into 5 degrees of severity 0 – none/very small, 1 – small, 2 – medium, 3 – large, 4 – very large disfigurements. In the third phase, 217 disfigurements were evaluated. Conclusion. The first 4-point ordinal scale was established, rating 217 disfigurements, which showed high level of compatibility in practice and which can be used as an instrument for standardization of disfigurements in giving of forensic expertise.